Penerapan Sistem Reward, Punishment dan Disiplin Kerja Karyawan Shift di PT Surya Pratista Hutama - Dhea Wulanjani; Sita Eka; Alfina Hikmah; Hesti Munawaron; Rindi Purwanto; Dwi Prihati; Adji Seputro (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
This study aims to describe the implementation of a reward and punishment system on work discipline among shift workers at PT Surya Pratista Hutama. The background of this study is based on the importance of maintaining work discipline in a shift work system, which often faces challenges such as lateness, absenteeism, and procedural violations. The research method used is a qualitative method with a descriptive approach. Data were collected through in-depth interviews with management and employees, direct observation in the work environment, and company documentation studies. The results show that the implementation of rewards, such as performance bonuses and non-material awards, can increase employee motivation in complying with work regulations. Meanwhile, the provision of punishments in the form of verbal warnings, warning letters, and incentive deductions has proven effective in reducing the level of disciplinary violations. However, the effectiveness of this system is highly dependent on the consistency of implementation, clarity of rules, and perceptions of fairness among employees. In conclusion, a proportional and transparent combination of rewards and punishments can be an effective strategy to improve work discipline among shift workers at this company.